Parabolic triangles, poles and centroid relations - Choi, Si Chun (Array, 2020)
We investigate affine properties of centroids formed by three points on a parabola together with the polar triangle formed from the tangents. And we make a wide ranging conjecture about the extension of these results to general conics.